2007
DOI: 10.1016/j.rapm.2007.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Prilocaine Epidural Anesthesia Using Epidural Saline or Ringer’s Lactate Washout

Abstract: We concluded that a more rapid recovery of motor and sensory blockade in patients undergoing epidural anesthesia may be achieved by the use of an epidural washout with either bolus or infusion of 45 mL normal saline or Ringer's lactate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Regression of motor block after epidural washout was twice as fast as in the control group (17 vs 32 min). Motor recovery showed similar results to those of previous studies using local anaesthetic solution with or without adrenaline [1, 4–6]; however, the influence of epidural washout on the speed of sensory regression was less than on motor regression. This discrepancy between speeds of sensory and motor regression may be attributed to the diluting effect of epidural saline.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Regression of motor block after epidural washout was twice as fast as in the control group (17 vs 32 min). Motor recovery showed similar results to those of previous studies using local anaesthetic solution with or without adrenaline [1, 4–6]; however, the influence of epidural washout on the speed of sensory regression was less than on motor regression. This discrepancy between speeds of sensory and motor regression may be attributed to the diluting effect of epidural saline.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, progressive changes of the spinal column associated with aging have been postulated to produce a narrowing of the intervertebral foramina along the column. This was why we used a smaller volume (30 ml) of saline in our elderly patients than others (40–45 ml) [3–5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3] Rapid recovery of motor and sensory block in outpatient patients undergoing 2% prilocaine epidural anesthesia may be achieved by an epidural washout with either bolus or infusion of 45 mL NS or RL. [4] Thus, studies have shown benefits of epidural washout with crystalloid boluses or infusion, but the effectiveness of bolus of NS in nonobstetrical patients undergoing 0.5% bupivacaine epidural anesthesia has not been investigated. We designed this study to determine the relationship of the epidural NS bolus to the recovery of motor and sensory block and hemodynamic stability (blood pressure and heart rate) in nonobstetrical patients undergoing epidural anesthesia using 0.5% bupivacaine.…”
mentioning
confidence: 99%